Comparison of mixing layer heights determined using LiDAR, radiosonde, and numerical weather prediction model at a rural site in southern India. Issue 22 (17th November 2017) - Vishnu, R.; Kumar, Y. Bhavani; Sinha, P. R.; Rao, T. Narayana; James Jebaseelan Samuel, E.; Kumar, P.
ABSTRACT: There is no agreed reference method for accurately determination of mixing layer height (MLH) in the existing literature. In part, this is due to different definitions of the atmospheric boundary layer exist, depending on the quantities and the physical processes invoked. In addition, MLH during late afternoon transition period is highly challenging to determine and perform model simulations because of the rapid variations in turbulent kinetic energy. For the first time, MLH has been determined at remote tropical site of Gadanki, India (13.45°N, 79.17°E, 360 masl) using ground-based elastic backscatter LiDAR (EBL). This article focuses on the late afternoon transition period and compares it with MLH obtained from the EBL to concurrent radiosonde (RS) observations [MLH (RS)] and numerical models. Five different techniques have been applied to the EBL backscatter profiles for the determination of MLH. The mean of the five methods agreed to within 15% with the RS-derived MLH under various synoptic conditions at the site. This indicates the potential capability of continuous monitoring of MLH by our EBL system. However, MLH determined by Weather Research and Forecasting model and European Center for Medium-Range Weather Forecasts Re Analaysis (ERA)-interim reanalysis systematically underestimated of the MLH (LiDAR) by about 62% and 48%, respectively. The mean growth rate of diurnal evolution of MLH was found to about 120 and 200 m h −1 during winter and spring seasons, respectively.